Refleksi Pragmatisme terhadap Motivasi Belajar Matematika Siswa dalam Logika dan Cinta di Drama Korea - Wulansari, Tantya; Rani, Rani; Wahidin, Didin; Firmansyah, Eka (JURNAL PENDIDIKAN DAN KEWIRAUSAHAAN, 2024)
The impact of Covid-19 throughout the world has resulted in a decrease in students' motivation to learn mathematics. At that time , everyone was doing activities at home so students used gadgets to study which resulted in students being exposed to Hallyu. Hallyu is a culture in South Korea. South Korea is one of the countries that is currently the center of attention in cyberspace. In the current Gen Z generation, they prefer actors or artists from that country. This research analyzes the relationship between logic and love in Korean dramas on students' mathematics learning motivation using a pragmatism approach. By watching one of the Korean drama content entitled "Melancholia" as a case study, this research uses qualitative methods with an ethnographic design based on teenagers' mindsets towards education. The results of the analysis show that logic can increase learning motivation in mathematics and help think analytically, while emotional factors such as interpersonal love can influence students' learning motivation. The pragmatism approach is relevant in the context of mathematics education. The implications of this research strengthen students' learning motivation in mathematics education for effective learning. Therefore, logic and love in the Korean drama "Melancholia" can have a positive and negative impact on students' learning motivation in learning mathematics